2011
DOI: 10.1007/s11250-011-9873-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and pedigree analysis applied to conservation of animal genetic resources: the case of Brazilian Somali hair sheep

Abstract: The first registers of Somali sheep in Brazil are from the beginning of the 1900s. This breed, adapted to the dry climate and scarce food supply, is restricted in the northeast region of the country. Molecular marker technologies, especially those based on genotyping microsatellite and mtDNA loci, can be used in conjunction with breeding (pedigree analysis) and consequently the maintenance of genetic variation in herds. Animals from the Brazilian Somali Conservation Nuclei from Embrapa Sheep and Goats in Ceará… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 34 publications
1
29
0
5
Order By: Relevance
“…Em 1991, ocorreu aumento expressivo e abrupto, com valor máximo de 12,22%, e, no período de 1992 a 2010, o F apresentou relativa estabilização, com média de 7,49%. Se admitirmos que valor de F superior a 10% representa risco elevado para ocorrência de depressão por endogamia (Paiva et al, 2011), a raça Santa Inês, com exceção do ano de 1991, apresentou médias anuais dentro de limites satisfatórios. A ausência de endogamia verificada nos primeiros sete anos de formação da raça não foi resultante da inexistência de animais endogâmicos na população, mas sim do número reduzido de ancestrais conhecidos até então, o que impossibilitou a determinação desse parâmetro.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Em 1991, ocorreu aumento expressivo e abrupto, com valor máximo de 12,22%, e, no período de 1992 a 2010, o F apresentou relativa estabilização, com média de 7,49%. Se admitirmos que valor de F superior a 10% representa risco elevado para ocorrência de depressão por endogamia (Paiva et al, 2011), a raça Santa Inês, com exceção do ano de 1991, apresentou médias anuais dentro de limites satisfatórios. A ausência de endogamia verificada nos primeiros sete anos de formação da raça não foi resultante da inexistência de animais endogâmicos na população, mas sim do número reduzido de ancestrais conhecidos até então, o que impossibilitou a determinação desse parâmetro.…”
Section: Resultsunclassified
“…O estudo da estrutura populacional baseado em informações de pedigree, embora apresente algumas desvantagens, como a baixa integridade ou imprecisão dos dados para animais de produção (Ron et al, 1996), tem sido realizado em diferentes populações ovinas de diversas partes do mundo (Maiwashe & Blackburn, 2004;Goyache et al, 2010;Paiva et al, 2011;Ghafouri-Kesbi, 2012).…”
Section: Introductionunclassified
“…This result may be due to the small sample population (15 individuals), and due to the population being consolidated with planned genetic crosses established from breeding programs. Several studies using locally adapted or native breeds confirmed that these breeds have more number of loci in HWE when compared to more specialized breeds (McManus et al, 2010;Paiva et al, 2011a;Tolone et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of the population structure combined with information about genetic changes can influence future management actions and can be used to develop strategies for using a breed in a particular ecosystem as a model for genetic improvement programs [41]. Conservation programs using molecular tools are crucial for the providing information about the genetic diversity of locally adapted groups, thus allowing them to be included in production systems for integration of adaptation and rusticity features [12].…”
Section: Phylogeny and Population Structurementioning
confidence: 99%